Przesłanki odwołania warunkowego zwolnienia w ujęciu ewolucyjnym w dwudziestopięciolecie obowiązywania kodeksu karnego wykonawczego z 1997 roku – wybrane zagadnienia - Lachowski, Jerzy (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The study discusses the regulations specifying the grounds for revoking conditional release. In the author’s opinion, it is worth looking at this regulation from an evolutionary and systemic perspective and trying to answer the question whether the development of regulations relating to this legal structure is going in the right direction, or whether changes to the regulations that apply to it should be seriously considered.
Keywords: parole; grounds for appeal; criminal policy